Frozen zero lactose with full use of passion fruit (Passiflora edulis): product development and preparation of nutritional information (Research, Society and Development, 2022)
Over the years, industrial food production has been increasingly seeking to improve and develop products according to the needs and preferences of consumers. Lactose-free frozen is characterized as a healthier option when compared to conventional ice cream, in addition to being able to serve a specific audience. The objective was to develop a lactose-free frozen product, taking full advantage of the passion fruit and preparing a table with nutritional information on the product. The yogurt was made from the union of zero lactose whole milk and sugar (10%), which was stored under refrigeration for later preparation of frozen. To obtain the passion fruit concentrate, the fruits were sanitized, the seeds separated and the peels reserved. For the production of the concentrate, pulp without seed (80%) was used, which was mixed with sugar (20%). The jam to finish the presentation was made with a mixture of passion fruit pulp (including seeds), sugar and water. Pectin, used as a gelling agent, was extracted from passion fruit peel. For the elaboration of the nutritional information table, a standard technical sheet was used, in which the ingredients were listed in homemade measures, in gross weight, in addition to the Brazilian Food Composition Table - TACO. With lactose-free frozen passion fruit yogurt, it was possible to develop a product with a lower degree of processing, absence of food additives and higher micronutrient content, being, therefore, more nutritious. The lactose-free Frozen Passion Fruit Yogurt, in addition to meeting the demand of lactose intolerant people, meets nutritional needs, contributes to health benefits and provides a better quality of life for consumers.